Three-dimensional porous high-entropy alloy reinforced aluminum-based composite material and preparation method thereof
By using three-dimensional porous high-entropy alloy as reinforcement in aluminum-based composite materials, the problem of insufficient strength and hardness of existing materials is solved, and the effects of high strength, high hardness and good interface bonding are achieved.
Patent Information
- Application Number
- CN202510219015.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-02-26
- Publication Date
- 2025-03-25
- Estimated Expiration
- 2045-02-26
AI Technical Summary
The existing aluminum-based composite materials have shortcomings in strength and hardness, and the interface bonding between the reinforcement body and the substrate is poor, which affects the material performance.
A three-dimensional porous high-entropy alloy is used as the reinforcement and is prepared by mechanical alloying ball milling, cold press forming, presintering, nitriding treatment and other steps to form a three-dimensional connected open pore structure combined with the aluminum alloy matrix.
It improves the comprehensive mechanical properties of the material, including high strength, high hardness, good interfacial bonding and isotropy, and enhances the stability and corrosion resistance of the material.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of alloys, and in particular to a three-dimensional porous high-entropy alloy reinforced aluminum-based composite material. Background Art
[0002] Aluminum-based composites are one of the most studied and widely used materials in metal-based composites. With the advantages of low density, high specific strength and specific stiffness, wear resistance and fatigue resistance, low thermal expansion coefficient, good electrical and thermal conductivity, and abundant aluminum resources, it is easy to process into plastic materials, which can significantly reduce industrial manufacturing costs. Therefore, it has a wide range of applications and is used in many industries such as aerospace, military, electronics, automobiles, and sports. The reinforcements of aluminum-based composites include particles, whiskers (discontinuous short fibers) and continuous long fibers. Different types of reinforcements have different characteristics. The fiber itself has high strength and modulus, so the long fiber reinforcement effect is better, but it is anisotropic, and the axial and lateral reinforcement effects are very different; although discontinuous short fibers and particles show isotropy, the agglomeration problem inside the material is difficult to solve, which has a great impact on the performance of the material. The commonly used reinforcement components of aluminum-based composites are mainly non-metals or ceramics such as boron, carbon (graphite), aluminum oxide, silicon carbide, and titanium boride. These reinforcements can effectively improve the strength and hardness of the material, but the cost is usually a decrease in plasticity. In addition, poor wettability and interface reaction problems between the reinforcement and the aluminum alloy matrix will also affect the performance of aluminum-based composites.
[0003] As modern technology places increasingly higher demands on material performance, it is particularly important to develop new aluminum-based composite materials, especially to find more suitable composite reinforcements and corresponding more complete preparation processes to further improve the performance of aluminum-based composite materials. Summary of the invention
[0004] Technical problem to be solved: The technical problem to be solved by the present invention is to provide a three-dimensional porous high-entropy alloy reinforced aluminum-based composite material, which has high strength, high hardness and excellent comprehensive mechanical properties.
[0005] Technical solution: A three-dimensional porous high-entropy alloy reinforced aluminum-based composite material, consisting of 60~70% aluminum alloy matrix and 30~40% three-dimensional porous high-entropy alloy, wherein the three-dimensional porous high-entropy alloy is a three-dimensionally connected open-pore structure with a porosity of 60~70% and a 1~2 μm nitride layer on the surface.
[0006] Preferably, the method for preparing the three-dimensional porous high entropy alloy reinforced aluminum-based composite material comprises the following steps: S1. The raw material powders required for the high entropy alloy are prepared in proportion, and mechanical alloying and ball milling are performed to mix them uniformly, and a pore-forming agent and a binder are added and ball milled again to mix them uniformly and form a paste to obtain a uniform raw material; S2. The raw material prepared in S1 is placed in a mold, cold pressed and dried, placed in a vacuum sintering furnace for pre-sintering, the pore-forming agent is removed in a water bath and dried, and then secondary sintered by plasma discharge sintering to obtain a three-dimensional porous high entropy alloy; S3. The three-dimensional porous high entropy alloy prepared in S2 is cleaned, placed in a plasma nitriding device, introduced into a mixed atmosphere of hydrogen and nitrogen and heated for nitridation, and then cooled to room temperature to obtain a three-dimensional porous high entropy alloy having a nitrided layer on the surface; S4. Place the three-dimensional porous high entropy alloy prepared in S3 at the bottom and the aluminum alloy at the top in a crucible and evacuate the crucible, preheat the three-dimensional porous high entropy alloy, then heat to melt the aluminum alloy and fill it with argon to pressurize it, maintain the temperature and pressure until the infiltration is completed and then solidify to obtain a three-dimensional porous high entropy alloy reinforced aluminum-based composite material.
[0007] Preferably, the mechanical alloying ball milling speed in step S1 is 300 to 350 r / min, and the ball milling time is 20 to 24 h.
[0008] Preferably, in step S1, the pore-forming agent is NaCl, the particle size is 200-300 μm, and the amount of NaCl added is 100-150% of the volume of the metal powder; the binder is anhydrous ethanol, and the amount of anhydrous ethanol added is 7-10% of the mass of the metal powder.
[0009] Preferably, the pre-sintering temperature in step S2 is 750-800°C, and the holding time is 4-6 h; the secondary sintering temperature is 1100-1300°C, and the holding time is 3-5 h.
[0010] Preferably, the heating temperature in step S3 is 480-520° C., the nitriding time is 1-2 h, and the ratio of nitrogen to hydrogen in the mixed atmosphere is 1:1-2.
[0011] Preferably, the preheating temperature of the three-dimensional porous high entropy alloy in step S4 is 400 ~ 420 ° C, and the heating temperature of the molten aluminum alloy is 720 ~ 780 ° C.
[0012] Preferably, the composition of the aluminum alloy matrix consists of the following weight percentages: Zn: 5.5 ~ 6.0 wt%, Mg: 2.0 ~ 2.5 wt%, Cu: 1.3 ~ 1.7 wt%, Cr: 0.15 ~ 0.33 wt%, Fe: ≤0.15 wt%, Si: ≤0.1wt%, and the balance is Al.
[0013] Preferably, the composition of the three-dimensional porous high entropy alloy is Ti 20-25 Mg 20-25 Fe 15-20 Cr 15-20 Ni 10-15 La 5-10 , and 1 ~ 5% Y2O3 was added.
[0014] Beneficial effects: The aluminum-based composite material of the present invention adopts a three-dimensional porous high-entropy alloy as a reinforcement, which not only has high strength and hardness, but also has good interface bonding with the matrix. At the same time, the three-dimensional structure makes the material isotropic, thereby improving the comprehensive performance of the material.
[0015] Ceramics are commonly used reinforcements for aluminum-based composites, which can significantly improve the strength and hardness of the material. However, the wettability and bonding between the two are poor. High entropy alloys have high configuration entropy and tend to form simple solid solution structures such as FCC and BCC rather than intermetallic compounds. Therefore, they have excellent comprehensive properties, such as high strength, high and low temperature toughness, thermal stability, wear resistance, corrosion resistance, etc. Not only are they not inferior to ceramics in comprehensive performance, but they also have the advantage of good metal-metal interface bonding with the aluminum matrix, making them ideal reinforcements for metal-based composites. High entropy alloys are prepared into a three-dimensional connected open-pore structure as a reinforcement for aluminum-based composites, forming a three-dimensional interpenetrating structure with the matrix, which can solve the problem of unstable material performance caused by uneven dispersion of the reinforcement phase and performance differences in different orientations of the material caused by the anisotropy of the reinforcement phase. In addition, porous materials have a large specific surface area and a large contact surface with the matrix, which is conducive to further improving the bonding force between the two phases and improving the stability of the material. Adding a small amount of Y2O3 during the sintering process of high-entropy alloys can effectively reduce the porosity of sintered parts, improve the sintering quality, and make the impurities in the material dispersed, reducing the impact of impurities on the performance of high-entropy alloys, while refining the grains, further improving the strength, hardness and corrosion resistance of the material. In addition, plasma nitriding treatment of three-dimensional porous high-entropy alloys to form a nitride film on its surface can increase the surface roughness of the alloy, improve the bonding force between the matrix and the high-entropy alloy, and reduce the diffusion of elements between the two interfaces, so that the reinforcement phase can still maintain a stable composition during the casting process and in high-temperature working environments. In addition, the nitride film can also improve the hardness and corrosion resistance of the high-entropy alloy and optimize the comprehensive performance of the material.
[0016] Compared with the prior art, the present invention has the following advantages and positive effects: The present invention adds a high-entropy alloy with high strength and high hardness as a composite material reinforcement, which can effectively improve the mechanical properties of the material, and at the same time form a metal-metal interface with the matrix, with strong bonding force and good material stability.
[0017] The invention prepares the reinforcement into a three-dimensional porous network form, solves the anisotropy problem of the fiber reinforcement and the uneven distribution problem of the particle reinforcement, and improves the comprehensive performance of the material.
[0018] The present invention adopts a pressure infiltration method to prepare the composite material, which can reduce the defects of the material and the interface reaction between the two phases and improve the performance and quality of the material. DETAILED DESCRIPTION In order to further understand the present invention, preferred embodiments of the present invention are described below in conjunction with examples.
[0020] Specific preferred examples are as follows: Embodiment 1:
[0021] A three-dimensional porous high-entropy alloy reinforced aluminum-based composite material, consisting of 70% aluminum alloy matrix and 30% three-dimensional porous high-entropy alloy, wherein the three-dimensional porous high-entropy alloy is a three-dimensionally connected open-pore structure with a porosity of 70% and a 1-2 μm nitride layer on the surface; The preparation method of the three-dimensional porous high entropy alloy reinforced aluminum-based composite material comprises the following steps: S1. The raw material powders required for high entropy alloy are prepared in proportion, and mechanical alloying ball milling is performed to mix them evenly. The ball milling speed is 320 r / min, and the ball milling time is 24 h. The pore-forming agent NaCl particles with a particle size of 200 ~ 300 μm and the binder anhydrous ethanol are added and ball milled again to mix them evenly and become a paste. The amount of pore-forming agent added is 150% of the volume of the metal powder, and the amount of binder added is 8% of the mass of the metal powder to obtain a uniform raw material; S2. The raw material prepared in S1 is placed in a mold, cold pressed and dried, and placed in a vacuum sintering furnace for pre-sintering at a temperature of 780 °C for 5 h. The pore-forming agent is removed in a water bath and dried. Then, a secondary sintering is performed by plasma discharge sintering at a temperature of 1100 °C for 4 h to obtain a three-dimensional porous high-entropy alloy. S3. The three-dimensional porous high entropy alloy prepared in S2 is cleaned, placed in a plasma nitriding device, introduced with a mixed atmosphere of nitrogen and hydrogen in a ratio of 1:2, and heated to 500 °C for nitriding for 1.5 h, and then cooled to room temperature to obtain a three-dimensional porous high entropy alloy with a nitrided layer on the surface; S4. The three-dimensional porous high entropy alloy prepared in S3 is placed in a crucible with the aluminum alloy at the bottom and evacuated, heated to 400 ° C to preheat the three-dimensional porous high entropy alloy, and then heated to 720 ° C to melt the aluminum alloy and pressurized with argon gas, and the temperature and pressure are maintained until the infiltration is completed and then solidified to obtain a three-dimensional porous high entropy alloy reinforced aluminum-based composite material; The aluminum alloy matrix comprises the following weight percentages: Zn: 5.5 wt%, Mg: 2.44 wt%, Cu: 1.52 wt%, Cr: 0.17 wt%, Fe: 0.12 wt%, Si: 0.1 wt%, and the balance is Al; The composition of the three-dimensional porous high entropy alloy is Ti 25 Mg 20 Fe 20 Cr 15 Ni 15 La5, and 1% Y2O3 was added. Embodiment 2:
[0022] A three-dimensional porous high-entropy alloy reinforced aluminum-based composite material, consisting of 65% aluminum alloy matrix and 35% three-dimensional porous high-entropy alloy, wherein the three-dimensional porous high-entropy alloy is a three-dimensionally connected open-pore structure with a porosity of 65% and a 1-2 μm nitride layer on the surface; The preparation method of the three-dimensional porous high entropy alloy reinforced aluminum-based composite material comprises the following steps: S1. The raw material powders required for high entropy alloy are prepared in proportion, and mechanical alloying ball milling is performed to mix them evenly. The ball milling speed is 320 r / min, and the ball milling time is 24 h. The pore-forming agent NaCl particles with a particle size of 200 ~ 300 μm and the binder anhydrous ethanol are added and ball milled again to mix them evenly and become a paste. The amount of pore-forming agent added is 125% of the volume of the metal powder, and the amount of binder added is 8% of the mass of the metal powder to obtain a uniform raw material; S2. The raw material prepared in S1 is placed in a mold, cold pressed and dried, and placed in a vacuum sintering furnace for pre-sintering at a temperature of 780 °C for 5 h. The pore-forming agent is removed in a water bath and dried. Then, a secondary sintering is performed by plasma discharge sintering at a temperature of 1100 °C for 4 h to obtain a three-dimensional porous high-entropy alloy. S3. The three-dimensional porous high entropy alloy prepared in S2 is cleaned, placed in a plasma nitriding device, introduced with a mixed atmosphere of nitrogen and hydrogen in a ratio of 1:2, and heated to 500 °C for nitriding for 1.5 h, and then cooled to room temperature to obtain a three-dimensional porous high entropy alloy with a nitrided layer on the surface; S4. The three-dimensional porous high entropy alloy prepared in S3 is placed in a crucible with the aluminum alloy at the bottom and evacuated, heated to 400 ° C to preheat the three-dimensional porous high entropy alloy, and then heated to 720 ° C to melt the aluminum alloy and pressurized with argon gas, and the temperature and pressure are maintained until the infiltration is completed and then solidified to obtain a three-dimensional porous high entropy alloy reinforced aluminum-based composite material; The aluminum alloy matrix comprises the following weight percentages: Zn: 5.94 wt%, Mg: 2.0 wt%, Cu: 1.33 wt%, Cr: 0.31 wt%, Fe: 0.15 wt%, and the balance is Al; The composition of the three-dimensional porous high entropy alloy is Ti 25 Mg 20 Fe 20 Cr 15 Ni 15 La5, and 1% Y2O3 was added. Embodiment 3:
[0023] A three-dimensional porous high-entropy alloy reinforced aluminum-based composite material, consisting of 60% aluminum alloy matrix and 40% three-dimensional porous high-entropy alloy, wherein the three-dimensional porous high-entropy alloy is a three-dimensionally connected open-pore structure with a porosity of 60% and a 1-2 μm nitride layer on the surface; The preparation method of the three-dimensional porous high entropy alloy reinforced aluminum-based composite material comprises the following steps: S1. The raw material powders required for high entropy alloy are prepared in proportion, and mechanical alloying ball milling is performed to mix them uniformly. The ball milling speed is 320 r / min, and the ball milling time is 24 h. The pore-forming agent NaCl particles with a particle size of 200 ~ 300 μm and the binder anhydrous ethanol are added and ball milled again to mix them uniformly and become a paste. The amount of pore-forming agent added is 100% of the volume of the metal powder, and the amount of binder added is 8% of the mass of the metal powder to obtain a uniform raw material; S2. The raw material prepared in S1 is placed in a mold, cold pressed and dried, and placed in a vacuum sintering furnace for pre-sintering at a temperature of 780 °C for 5 h. The pore-forming agent is removed in a water bath and dried. Then, a secondary sintering is performed by plasma discharge sintering at a temperature of 1100 °C for 4 h to obtain a three-dimensional porous high-entropy alloy. S3. The three-dimensional porous high entropy alloy prepared in S2 is cleaned, placed in a plasma nitriding device, introduced with a mixed atmosphere of nitrogen and hydrogen in a ratio of 1:2, and heated to 500 °C for nitriding for 1.5 h, and then cooled to room temperature to obtain a three-dimensional porous high entropy alloy with a nitrided layer on the surface; S4. The three-dimensional porous high entropy alloy prepared in S3 is placed in a crucible with the aluminum alloy at the bottom and evacuated, heated to 400 ° C to preheat the three-dimensional porous high entropy alloy, and then heated to 720 ° C to melt the aluminum alloy and pressurized with argon gas, and the temperature and pressure are maintained until the infiltration is completed and then solidified to obtain a three-dimensional porous high entropy alloy reinforced aluminum-based composite material; The aluminum alloy matrix comprises the following weight percentages: Zn: 5.76 wt%, Mg: 2.23 wt%, Cu: 1.7 wt%, Cr: 0.20 wt%, Fe: 0.06 wt%, Si: 0.05 wt%, and the balance is Al; The composition of the three-dimensional porous high entropy alloy is Ti 25 Mg 20 Fe 20 Cr 15 Ni 15 La5, and 1% Y2O3 was added. Embodiment 4:
[0024] A three-dimensional porous high-entropy alloy reinforced aluminum-based composite material, consisting of 65% aluminum alloy matrix and 35% three-dimensional porous high-entropy alloy, wherein the three-dimensional porous high-entropy alloy is a three-dimensionally connected open-pore structure with a porosity of 65% and a 1-2 μm nitride layer on the surface; The preparation method of the three-dimensional porous high entropy alloy reinforced aluminum-based composite material comprises the following steps: S1. The raw material powders required for high entropy alloy are prepared in proportion, and mechanical alloying ball milling is performed to mix them evenly. The ball milling speed is 320 r / min, and the ball milling time is 24 h. The pore-forming agent NaCl particles with a particle size of 200 ~ 300 μm and the binder anhydrous ethanol are added and ball milled again to mix them evenly and become a paste. The amount of pore-forming agent added is 125% of the volume of the metal powder, and the amount of binder added is 8% of the mass of the metal powder to obtain a uniform raw material; S2. The raw material prepared in S1 is placed in a mold, cold pressed and dried, and placed in a vacuum sintering furnace for pre-sintering at a temperature of 780 °C for 5 h. The pore-forming agent is removed in a water bath and dried. Then, a secondary sintering is performed by plasma discharge sintering at a temperature of 1150 °C for 4 h to obtain a three-dimensional porous high-entropy alloy. S3. The three-dimensional porous high entropy alloy prepared in S2 is cleaned, placed in a plasma nitriding device, introduced with a mixed atmosphere of nitrogen and hydrogen in a ratio of 1:2, and heated to 500 °C for nitriding for 1.5 h, and then cooled to room temperature to obtain a three-dimensional porous high entropy alloy with a nitrided layer on the surface; S4. The three-dimensional porous high entropy alloy prepared in S3 is placed in a crucible with the aluminum alloy at the bottom and evacuated, heated to 400 ° C to preheat the three-dimensional porous high entropy alloy, and then heated to 720 ° C to melt the aluminum alloy and pressurized with argon gas, and the temperature and pressure are maintained until the infiltration is completed and then solidified to obtain a three-dimensional porous high entropy alloy reinforced aluminum-based composite material; The aluminum alloy matrix comprises the following weight percentages: Zn: 5.88 wt%, Mg: 2.37 wt%, Cu: 1.42 wt%, Cr: 0.33 wt%, Si: 0.08 wt%, and the balance is Al; The composition of the three-dimensional porous high entropy alloy is Ti 25 Mg 20 Fe 20 Cr 15 Ni 15 La5, and 1% Y2O3 was added. Embodiment 5:
[0025] A three-dimensional porous high-entropy alloy reinforced aluminum-based composite material, consisting of 65% aluminum alloy matrix and 35% three-dimensional porous high-entropy alloy, wherein the three-dimensional porous high-entropy alloy is a three-dimensionally connected open-pore structure with a porosity of 65% and a 1-2 μm nitride layer on the surface; The preparation method of the three-dimensional porous high entropy alloy reinforced aluminum-based composite material comprises the following steps: S1. The raw material powders required for high entropy alloy are prepared in proportion, and mechanical alloying ball milling is performed to mix them evenly. The ball milling speed is 320 r / min, and the ball milling time is 24 h. The pore-forming agent NaCl particles with a particle size of 200 ~ 300 μm and the binder anhydrous ethanol are added and ball milled again to mix them evenly and become a paste. The amount of pore-forming agent added is 125% of the volume of the metal powder, and the amount of binder added is 8% of the mass of the metal powder to obtain a uniform raw material; S2. The raw material prepared in S1 is placed in a mold, cold pressed and dried, and placed in a vacuum sintering furnace for pre-sintering at a temperature of 780 °C for 5 h. The pore-forming agent is removed in a water bath and dried. Then, a secondary sintering is performed by plasma discharge sintering at a temperature of 1200 °C for 4 h to obtain a three-dimensional porous high-entropy alloy. S3. The three-dimensional porous high entropy alloy prepared in S2 is cleaned, placed in a plasma nitriding device, introduced with a mixed atmosphere of nitrogen and hydrogen in a ratio of 1:2, and heated to 500 °C for nitriding for 1.5 h, and then cooled to room temperature to obtain a three-dimensional porous high entropy alloy with a nitrided layer on the surface; S4. The three-dimensional porous high entropy alloy prepared in S3 is placed in a crucible with the aluminum alloy at the bottom and evacuated, heated to 400 ° C to preheat the three-dimensional porous high entropy alloy, and then heated to 720 ° C to melt the aluminum alloy and pressurized with argon gas, and the temperature and pressure are maintained until the infiltration is completed and then solidified to obtain a three-dimensional porous high entropy alloy reinforced aluminum-based composite material; The aluminum alloy matrix comprises the following weight percentages: Zn: 5.57 wt%, Mg: 2.15 wt%, Cu: 1.52 wt%, Cr: 0.18 wt%, Fe: 0.11 wt%, Si: 0.04 wt%, and the balance is Al; The composition of the three-dimensional porous high entropy alloy is Ti 25 Mg 20 Fe 20 Cr 15 Ni 15 La5, and 1% Y2O3 was added. Embodiment 6:
[0026] A three-dimensional porous high-entropy alloy reinforced aluminum-based composite material, consisting of 65% aluminum alloy matrix and 35% three-dimensional porous high-entropy alloy, wherein the three-dimensional porous high-entropy alloy is a three-dimensionally connected open-pore structure with a porosity of 65% and a 1-2 μm nitride layer on the surface; The preparation method of the three-dimensional porous high entropy alloy reinforced aluminum-based composite material comprises the following steps: S1. The raw material powders required for high entropy alloy are prepared in proportion, and mechanical alloying ball milling is performed to mix them evenly. The ball milling speed is 320 r / min, and the ball milling time is 24 h. The pore-forming agent NaCl particles with a particle size of 200 ~ 300 μm and the binder anhydrous ethanol are added and ball milled again to mix them evenly and become a paste. The amount of pore-forming agent added is 125% of the volume of the metal powder, and the amount of binder added is 8% of the mass of the metal powder to obtain a uniform raw material; S2. The raw material prepared in S1 is placed in a mold, cold pressed and dried, and placed in a vacuum sintering furnace for pre-sintering at a temperature of 780 °C for 5 h. The pore-forming agent is removed in a water bath and dried. Then, a secondary sintering is performed by plasma discharge sintering at a temperature of 1250 °C for 4 h to obtain a three-dimensional porous high-entropy alloy. S3. The three-dimensional porous high entropy alloy prepared in S2 is cleaned, placed in a plasma nitriding device, introduced with a mixed atmosphere of nitrogen and hydrogen in a ratio of 1:2, and heated to 500 °C for nitriding for 1.5 h, and then cooled to room temperature to obtain a three-dimensional porous high entropy alloy with a nitrided layer on the surface; S4. The three-dimensional porous high entropy alloy prepared in S3 is placed in a crucible with the aluminum alloy at the bottom and evacuated, heated to 400 ° C to preheat the three-dimensional porous high entropy alloy, and then heated to 720 ° C to melt the aluminum alloy and pressurized with argon gas, and the temperature and pressure are maintained until the infiltration is completed and then solidified to obtain a three-dimensional porous high entropy alloy reinforced aluminum-based composite material; The aluminum alloy matrix comprises the following weight percentages: Zn: 5.94 wt%, Mg: 2.13 wt%, Cu: 1.32 wt%, Cr: 0.20 wt%, Fe: 0.15 wt%, Si: 0.05 wt%, and the balance is Al; The composition of the three-dimensional porous high entropy alloy is Ti 25 Mg 20 Fe 20 Cr 15 Ni 15 La5, and 1% Y2O3 was added. Embodiment 7:
[0027] A three-dimensional porous high-entropy alloy reinforced aluminum-based composite material, consisting of 65% aluminum alloy matrix and 35% three-dimensional porous high-entropy alloy, wherein the three-dimensional porous high-entropy alloy is a three-dimensionally connected open-pore structure with a porosity of 65% and a 1-2 μm nitride layer on the surface; The preparation method of the three-dimensional porous high entropy alloy reinforced aluminum-based composite material comprises the following steps: S1. The raw material powders required for high entropy alloy are prepared in proportion, and mechanical alloying ball milling is performed to mix them evenly. The ball milling speed is 320 r / min, and the ball milling time is 24 h. The pore-forming agent NaCl particles with a particle size of 200 ~ 300 μm and the binder anhydrous ethanol are added and ball milled again to mix them evenly and become a paste. The amount of pore-forming agent added is 125% of the volume of the metal powder, and the amount of binder added is 8% of the mass of the metal powder to obtain a uniform raw material; S2. The raw material prepared in S1 is placed in a mold, cold pressed and dried, and placed in a vacuum sintering furnace for pre-sintering at a temperature of 780 °C for 5 h. The pore-forming agent is removed in a water bath and dried. Then, a secondary sintering is performed by plasma discharge sintering at a temperature of 1300 °C for 4 h to obtain a three-dimensional porous high-entropy alloy. S3. The three-dimensional porous high entropy alloy prepared in S2 is cleaned, placed in a plasma nitriding device, introduced with a mixed atmosphere of nitrogen and hydrogen in a ratio of 1:2, and heated to 500 °C for nitriding for 1.5 h, and then cooled to room temperature to obtain a three-dimensional porous high entropy alloy with a nitrided layer on the surface; S4. The three-dimensional porous high entropy alloy prepared in S3 is placed in a crucible with the aluminum alloy at the bottom and evacuated, heated to 400 ° C to preheat the three-dimensional porous high entropy alloy, and then heated to 720 ° C to melt the aluminum alloy and pressurized with argon gas, and the temperature and pressure are maintained until the infiltration is completed and then solidified to obtain a three-dimensional porous high entropy alloy reinforced aluminum-based composite material; The aluminum alloy matrix comprises the following weight percentages: Zn: 5.62 wt%, Mg: 2.42 wt%, Cu: 1.64 wt%, Cr: 0.30 wt%, Fe: 0.04 wt%, Si: 0.09 wt%, and the balance is Al; The composition of the three-dimensional porous high entropy alloy is Ti 25 Mg 20 Fe 20 Cr 15 Ni 15 La5, and 1% Y2O3 was added. Embodiment 8:
[0028] A three-dimensional porous high-entropy alloy reinforced aluminum-based composite material, consisting of 65% aluminum alloy matrix and 35% three-dimensional porous high-entropy alloy, wherein the three-dimensional porous high-entropy alloy is a three-dimensionally connected open-pore structure with a porosity of 65% and a 1-2 μm nitride layer on the surface; The preparation method of the three-dimensional porous high entropy alloy reinforced aluminum-based composite material comprises the following steps: S1. The raw material powders required for high entropy alloy are prepared in proportion, and mechanical alloying ball milling is performed to mix them evenly. The ball milling speed is 320 r / min, and the ball milling time is 24 h. The pore-forming agent NaCl particles with a particle size of 200 ~ 300 μm and the binder anhydrous ethanol are added and ball milled again to mix them evenly and become a paste. The amount of pore-forming agent added is 125% of the volume of the metal powder, and the amount of binder added is 8% of the mass of the metal powder to obtain a uniform raw material; S2. The raw material prepared in S1 is placed in a mold, cold pressed and dried, and placed in a vacuum sintering furnace for pre-sintering at a temperature of 780 °C for 5 h. The pore-forming agent is removed in a water bath and dried. Then, a secondary sintering is performed by plasma discharge sintering at a temperature of 1250 °C for 4 h to obtain a three-dimensional porous high-entropy alloy. S3. The three-dimensional porous high entropy alloy prepared in S2 is cleaned, placed in a plasma nitriding device, introduced with a mixed atmosphere of nitrogen and hydrogen in a ratio of 1:2, and heated to 500 °C for nitriding for 1.5 h, and then cooled to room temperature to obtain a three-dimensional porous high entropy alloy with a nitrided layer on the surface; S4. The three-dimensional porous high entropy alloy prepared in S3 is placed in a crucible with the aluminum alloy at the bottom and evacuated, heated to 400 ° C to preheat the three-dimensional porous high entropy alloy, and then heated to 740 ° C to melt the aluminum alloy and pressurized with argon gas, and the temperature and pressure are maintained until the infiltration is completed and then solidified to obtain a three-dimensional porous high entropy alloy reinforced aluminum-based composite material; The aluminum alloy matrix comprises the following weight percentages: Zn: 5.62 wt%, Mg: 2.47 wt%, Cu: 1.55 wt%, Cr: 0.24 wt%, Fe: 0.12 wt%, Si: 0.08 wt%, and the balance is Al; The composition of the three-dimensional porous high entropy alloy is Ti 25 Mg 20 Fe 20 Cr 15 Ni 15 La5, and 1% Y2O3 was added. Embodiment 9:
[0029] A three-dimensional porous high-entropy alloy reinforced aluminum-based composite material, consisting of 65% aluminum alloy matrix and 35% three-dimensional porous high-entropy alloy, wherein the three-dimensional porous high-entropy alloy is a three-dimensionally connected open-pore structure with a porosity of 65% and a 1-2 μm nitride layer on the surface; The preparation method of the three-dimensional porous high entropy alloy reinforced aluminum-based composite material comprises the following steps: S1. The raw material powders required for high entropy alloy are prepared in proportion, and mechanical alloying ball milling is performed to mix them evenly. The ball milling speed is 320 r / min, and the ball milling time is 24 h. The pore-forming agent NaCl particles with a particle size of 200 ~ 300 μm and the binder anhydrous ethanol are added and ball milled again to mix them evenly and become a paste. The amount of pore-forming agent added is 125% of the volume of the metal powder, and the amount of binder added is 8% of the mass of the metal powder to obtain a uniform raw material; S2. The raw material prepared in S1 is placed in a mold, cold pressed and dried, and placed in a vacuum sintering furnace for pre-sintering at a temperature of 780 °C for 5 h. The pore-forming agent is removed in a water bath and dried. Then, a secondary sintering is performed by plasma discharge sintering at a temperature of 1250 °C for 4 h to obtain a three-dimensional porous high-entropy alloy. S3. The three-dimensional porous high entropy alloy prepared in S2 is cleaned, placed in a plasma nitriding device, introduced with a mixed atmosphere of nitrogen and hydrogen in a ratio of 1:2, and heated to 500 °C for nitriding for 1.5 h, and then cooled to room temperature to obtain a three-dimensional porous high entropy alloy with a nitrided layer on the surface; S4. The three-dimensional porous high entropy alloy prepared in S3 is placed in a crucible with the aluminum alloy at the bottom and evacuated, heated to 400 ° C to preheat the three-dimensional porous high entropy alloy, and then heated to 760 ° C to melt the aluminum alloy and pressurize it with argon gas, and the temperature and pressure are maintained until the infiltration is completed and then solidified to obtain a three-dimensional porous high entropy alloy reinforced aluminum-based composite material; The aluminum alloy matrix comprises the following weight percentages: Zn: 5.75 wt%, Mg: 2.28 wt%, Cu: 1.46 wt%, Cr: 0.29 wt%, Fe: 0.09 wt%, Si: 0.09 wt%, and the balance is Al; The composition of the three-dimensional porous high entropy alloy is Ti 25 Mg 20 Fe 20 Cr 15 Ni 15 La5, and 1% Y2O3 was added.
[0030] Embodiment 10: A three-dimensional porous high-entropy alloy reinforced aluminum-based composite material, consisting of 65% aluminum alloy matrix and 35% three-dimensional porous high-entropy alloy, wherein the three-dimensional porous high-entropy alloy is a three-dimensionally connected open-pore structure with a porosity of 65% and a 1-2 μm nitride layer on the surface; The preparation method of the three-dimensional porous high entropy alloy reinforced aluminum-based composite material comprises the following steps: S1. The raw material powders required for high entropy alloy are prepared in proportion, and mechanical alloying ball milling is performed to mix them evenly. The ball milling speed is 320 r / min, and the ball milling time is 24 h. The pore-forming agent NaCl particles with a particle size of 200 ~ 300 μm and the binder anhydrous ethanol are added and ball milled again to mix them evenly and become a paste. The amount of pore-forming agent added is 125% of the volume of the metal powder, and the amount of binder added is 8% of the mass of the metal powder to obtain a uniform raw material; S2. The raw material prepared in S1 is placed in a mold, cold pressed and dried, and placed in a vacuum sintering furnace for pre-sintering at a temperature of 780 °C for 5 h. The pore-forming agent is removed in a water bath and dried. Then, a secondary sintering is performed by plasma discharge sintering at a temperature of 1250 °C for 4 h to obtain a three-dimensional porous high-entropy alloy. S3. The three-dimensional porous high entropy alloy prepared in S2 is cleaned, placed in a plasma nitriding device, introduced with a mixed atmosphere of nitrogen and hydrogen in a ratio of 1:2, and heated to 500 °C for nitriding for 1.5 h, and then cooled to room temperature to obtain a three-dimensional porous high entropy alloy with a nitrided layer on the surface; S4. The three-dimensional porous high entropy alloy prepared in S3 is placed in a crucible with the aluminum alloy at the bottom and evacuated, heated to 400 ° C to preheat the three-dimensional porous high entropy alloy, and then heated to 780 ° C to melt the aluminum alloy and pressurized with argon gas, and the temperature and pressure are maintained until the infiltration is completed and then solidified to obtain a three-dimensional porous high entropy alloy reinforced aluminum-based composite material; The aluminum alloy matrix comprises the following weight percentages: Zn: 5.69 wt%, Mg: 2.22 wt%, Cu: 1.56 wt%, Cr: 0.30 wt%, Fe: 0.14 wt%, Si: 0.03 wt%, and the balance is Al; The composition of the three-dimensional porous high entropy alloy is Ti 25 Mg 20 Fe 20 Cr 15 Ni 15 La5, and 1% Y2O3 was added.
[0031] Embodiment 11: A three-dimensional porous high-entropy alloy reinforced aluminum-based composite material, consisting of 65% aluminum alloy matrix and 35% three-dimensional porous high-entropy alloy, wherein the three-dimensional porous high-entropy alloy is a three-dimensionally connected open-pore structure with a porosity of 65% and a 1-2 μm nitride layer on the surface; The preparation method of the three-dimensional porous high entropy alloy reinforced aluminum-based composite material comprises the following steps: S1. The raw material powders required for high entropy alloy are prepared in proportion, and mechanical alloying ball milling is performed to mix them evenly. The ball milling speed is 320 r / min, and the ball milling time is 24 h. The pore-forming agent NaCl particles with a particle size of 200 ~ 300 μm and the binder anhydrous ethanol are added and ball milled again to mix them evenly and become a paste. The amount of pore-forming agent added is 125% of the volume of the metal powder, and the amount of binder added is 8% of the mass of the metal powder to obtain a uniform raw material; S2. The raw material prepared in S1 is placed in a mold, cold pressed and dried, and placed in a vacuum sintering furnace for pre-sintering at a temperature of 760 °C for 5 h. The pore-forming agent is removed in a water bath and dried. Then, a secondary sintering is performed by plasma discharge sintering at a temperature of 1250 °C for 4 h to obtain a three-dimensional porous high-entropy alloy. S3. The three-dimensional porous high entropy alloy prepared in S2 is cleaned, placed in a plasma nitriding device, introduced with a mixed atmosphere of nitrogen and hydrogen in a ratio of 1:2, and heated to 500 °C for nitriding for 1.5 h, and then cooled to room temperature to obtain a three-dimensional porous high entropy alloy with a nitrided layer on the surface; S4. The three-dimensional porous high entropy alloy prepared in S3 is placed in a crucible with the aluminum alloy at the bottom and evacuated, heated to 400 ° C to preheat the three-dimensional porous high entropy alloy, and then heated to 760 ° C to melt the aluminum alloy and pressurize it with argon gas, and the temperature and pressure are maintained until the infiltration is completed and then solidified to obtain a three-dimensional porous high entropy alloy reinforced aluminum-based composite material; The aluminum alloy matrix comprises the following weight percentages: Zn: 5.96 wt%, Mg: 2.05 wt%, Cu: 1.58 wt%, Cr: 0.17 wt%, Fe: 0.11 wt%, Si: 0.1 wt%, and the balance is Al; The composition of the three-dimensional porous high entropy alloy is Ti 25 Mg 20 Fe 20 Cr 15 Ni 15 La5, and 2% Y2O3 was added.
[0032] Embodiment 12: A three-dimensional porous high-entropy alloy reinforced aluminum-based composite material, consisting of 65% aluminum alloy matrix and 35% three-dimensional porous high-entropy alloy, wherein the three-dimensional porous high-entropy alloy is a three-dimensionally connected open-pore structure with a porosity of 65% and a 1-2 μm nitride layer on the surface; The preparation method of the three-dimensional porous high entropy alloy reinforced aluminum-based composite material comprises the following steps: S1. The raw material powders required for high entropy alloy are prepared in proportion, and mechanical alloying ball milling is performed to mix them evenly. The ball milling speed is 320 r / min, and the ball milling time is 24 h. The pore-forming agent NaCl particles with a particle size of 200 ~ 300 μm and the binder anhydrous ethanol are added and ball milled again to mix them evenly and become a paste. The amount of pore-forming agent added is 125% of the volume of the metal powder, and the amount of binder added is 8% of the mass of the metal powder to obtain a uniform raw material; S2. The raw material prepared in S1 is placed in a mold, cold pressed and dried, and placed in a vacuum sintering furnace for pre-sintering at a temperature of 760 °C for 5 h. The pore-forming agent is removed in a water bath and dried. Then, a secondary sintering is performed by plasma discharge sintering at a temperature of 1250 °C for 4 h to obtain a three-dimensional porous high-entropy alloy. S3. The three-dimensional porous high entropy alloy prepared in S2 is cleaned, placed in a plasma nitriding device, introduced with a mixed atmosphere of nitrogen and hydrogen in a ratio of 1:2, and heated to 500 °C for nitriding for 1.5 h, and then cooled to room temperature to obtain a three-dimensional porous high entropy alloy with a nitrided layer on the surface; S4. The three-dimensional porous high entropy alloy prepared in S3 is placed in a crucible with the aluminum alloy at the bottom and evacuated, heated to 400 ° C to preheat the three-dimensional porous high entropy alloy, and then heated to 760 ° C to melt the aluminum alloy and pressurize it with argon gas, and the temperature and pressure are maintained until the infiltration is completed and then solidified to obtain a three-dimensional porous high entropy alloy reinforced aluminum-based composite material; The aluminum alloy matrix comprises the following weight percentages: Zn: 5.94 wt%, Mg: 2.03 wt%, Cu: 1.35 wt%, Cr: 0.30 wt%, Fe: 0.06 wt%, Si: 0.05 wt%, and the balance is Al; The composition of the three-dimensional porous high entropy alloy is Ti 25 Mg 20 Fe 20 Cr 15 Ni 15 La5, and 3% Y2O3 was added.
[0033] Embodiment 13: A three-dimensional porous high-entropy alloy reinforced aluminum-based composite material, consisting of 65% aluminum alloy matrix and 35% three-dimensional porous high-entropy alloy, wherein the three-dimensional porous high-entropy alloy is a three-dimensionally connected open-pore structure with a porosity of 65% and a 1-2 μm nitride layer on the surface; The preparation method of the three-dimensional porous high entropy alloy reinforced aluminum-based composite material comprises the following steps: S1. The raw material powders required for high entropy alloy are prepared in proportion, and mechanical alloying ball milling is performed to mix them evenly. The ball milling speed is 320 r / min, and the ball milling time is 24 h. The pore-forming agent NaCl particles with a particle size of 200 ~ 300 μm and the binder anhydrous ethanol are added and ball milled again to mix them evenly and become a paste. The amount of pore-forming agent added is 125% of the volume of the metal powder, and the amount of binder added is 8% of the mass of the metal powder to obtain a uniform raw material; S2. The raw material prepared in S1 is placed in a mold, cold pressed and dried, and placed in a vacuum sintering furnace for pre-sintering at a temperature of 760 °C for 5 h. The pore-forming agent is removed in a water bath and dried. Then, a secondary sintering is performed by plasma discharge sintering at a temperature of 1250 °C for 4 h to obtain a three-dimensional porous high-entropy alloy. S3. The three-dimensional porous high entropy alloy prepared in S2 is cleaned, placed in a plasma nitriding device, introduced with a mixed atmosphere of nitrogen and hydrogen in a ratio of 1:2, and heated to 500 °C for nitriding for 1.5 h, and then cooled to room temperature to obtain a three-dimensional porous high entropy alloy with a nitrided layer on the surface; S4. The three-dimensional porous high entropy alloy prepared in S3 is placed in a crucible with the aluminum alloy at the bottom and evacuated, heated to 400 ° C to preheat the three-dimensional porous high entropy alloy, and then heated to 760 ° C to melt the aluminum alloy and pressurize it with argon gas, and the temperature and pressure are maintained until the infiltration is completed and then solidified to obtain a three-dimensional porous high entropy alloy reinforced aluminum-based composite material; The aluminum alloy matrix comprises the following weight percentages: Zn: 5.86 wt%, Mg: 2.44 wt%, Cu: 1.52 wt%, Cr: 0.19 wt%, Fe: 0.05 wt%, Si: 0.01 wt%, and the balance is Al; The composition of the three-dimensional porous high entropy alloy is Ti 25 Mg 20 Fe 20 Cr 15 Ni 15 La5, and 4% Y2O3 was added.
[0034] Embodiment 14: A three-dimensional porous high-entropy alloy reinforced aluminum-based composite material, consisting of 65% aluminum alloy matrix and 35% three-dimensional porous high-entropy alloy, wherein the three-dimensional porous high-entropy alloy is a three-dimensionally connected open-pore structure with a porosity of 65% and a 1-2 μm nitride layer on the surface; The preparation method of the three-dimensional porous high entropy alloy reinforced aluminum-based composite material comprises the following steps: S1. The raw material powders required for high entropy alloy are prepared in proportion, and mechanical alloying ball milling is performed to mix them evenly. The ball milling speed is 320 r / min, and the ball milling time is 24 h. The pore-forming agent NaCl particles with a particle size of 200 ~ 300 μm and the binder anhydrous ethanol are added and ball milled again to mix them evenly and become a paste. The amount of pore-forming agent added is 125% of the volume of the metal powder, and the amount of binder added is 8% of the mass of the metal powder to obtain a uniform raw material; S2. The raw material prepared in S1 is placed in a mold, cold pressed and dried, and placed in a vacuum sintering furnace for pre-sintering at a temperature of 760 °C for 5 h. The pore-forming agent is removed in a water bath and dried. Then, a secondary sintering is performed by plasma discharge sintering at a temperature of 1250 °C for 4 h to obtain a three-dimensional porous high-entropy alloy. S3. The three-dimensional porous high entropy alloy prepared in S2 is cleaned, placed in a plasma nitriding device, introduced with a mixed atmosphere of nitrogen and hydrogen in a ratio of 1:2, and heated to 500 °C for nitriding for 1.5 h, and then cooled to room temperature to obtain a three-dimensional porous high entropy alloy with a nitrided layer on the surface; S4. The three-dimensional porous high entropy alloy prepared in S3 is placed in a crucible with the aluminum alloy at the bottom and evacuated, heated to 400 ° C to preheat the three-dimensional porous high entropy alloy, and then heated to 760 ° C to melt the aluminum alloy and pressurize it with argon gas, and the temperature and pressure are maintained until the infiltration is completed and then solidified to obtain a three-dimensional porous high entropy alloy reinforced aluminum-based composite material; The aluminum alloy matrix comprises the following weight percentages: Zn: 5.53 wt%, Mg: 2.08 wt%, Cu: 1.62 wt%, Cr: 0.32 wt%, Fe: 0.13 wt%, Si: 0.04 wt%, and the balance is Al; The composition of the three-dimensional porous high entropy alloy is Ti 25 Mg 20 Fe 20 Cr 15 Ni 15 La5, and 5% Y2O3 was added.
[0035] In order to further illustrate the technical effect of the present invention, the present invention also provides a comparative example, which is as follows: Comparative Example 1: An aluminum-based composite material, consisting of 50% aluminum alloy matrix and 50% three-dimensional porous high-entropy alloy, wherein the three-dimensional porous high-entropy alloy is a three-dimensionally connected open-pore structure with a porosity of 50% and a 1-2 μm nitride layer on the surface; The preparation method of the aluminum-based composite material comprises the following steps: S1. The raw material powders required for high entropy alloy are prepared in proportion, and mechanical alloying ball milling is performed to mix them uniformly. The ball milling speed is 320 r / min, and the ball milling time is 24 h. The pore-forming agent NaCl particles with a particle size of 200 ~ 300 μm and the binder anhydrous ethanol are added and ball milled again to mix them uniformly and become a paste. The amount of pore-forming agent added is 70% of the volume of metal powder, and the amount of binder added is 8% of the mass of metal powder to obtain a uniform raw material; S2. The raw material prepared in S1 is placed in a mold, cold pressed and dried, and placed in a vacuum sintering furnace for pre-sintering at a temperature of 780 °C for 5 h. The pore-forming agent is removed in a water bath and dried. Then, a secondary sintering is performed by plasma discharge sintering at a temperature of 1100 °C for 4 h to obtain a three-dimensional porous high-entropy alloy. S3. The three-dimensional porous high entropy alloy prepared in S2 is cleaned, placed in a plasma nitriding device, introduced with a mixed atmosphere of nitrogen and hydrogen in a ratio of 1:2, and heated to 500 °C for nitriding for 1.5 h, and then cooled to room temperature to obtain a three-dimensional porous high entropy alloy with a nitrided layer on the surface; S4. The three-dimensional porous high entropy alloy prepared in S3 is placed in a crucible with the aluminum alloy at the bottom and evacuated, heated to 400 ° C to preheat the three-dimensional porous high entropy alloy, and then heated to 720 ° C to melt the aluminum alloy and pressurize it with argon gas, and the temperature and pressure are maintained until the infiltration is completed and solidified to obtain an aluminum-based composite material; The aluminum alloy matrix comprises the following weight percentages: Zn: 5.89 wt%, Mg: 2.06 wt%, Cu: 1.66 wt%, Cr: 0.27 wt%, Fe: 0.08 wt%, Si: 0.05 wt%, and the balance is Al; The composition of the three-dimensional porous high entropy alloy is Ti 25 Mg 20 Fe 20 Cr 15 Ni 15 La5, and 1% Y2O3 was added.
[0036] Comparative Example 2: An aluminum-based composite material, consisting of 65% aluminum alloy matrix and 35% three-dimensional porous high-entropy alloy, wherein the three-dimensional porous high-entropy alloy is a three-dimensionally connected open-pore structure with a porosity of 65% and a 1-2 μm nitride layer on the surface; The preparation method of the aluminum-based composite material comprises the following steps: S1. The raw material powders required for high entropy alloy are prepared in proportion, and mechanical alloying ball milling is performed to mix them evenly. The ball milling speed is 320 r / min, and the ball milling time is 24 h. The pore-forming agent NaCl particles with a particle size of 200 ~ 300 μm and the binder anhydrous ethanol are added and ball milled again to mix them evenly and become a paste. The amount of pore-forming agent added is 125% of the volume of the metal powder, and the amount of binder added is 8% of the mass of the metal powder to obtain a uniform raw material; S2. The raw material prepared in S1 is placed in a mold, cold pressed and dried, and placed in a vacuum sintering furnace for pre-sintering at a temperature of 780 °C for 5 h. The pore-forming agent is removed in a water bath and dried. Then, a secondary sintering is performed by plasma discharge sintering at a temperature of 1000 °C for 4 h to obtain a three-dimensional porous high-entropy alloy. S3. The three-dimensional porous high entropy alloy prepared in S2 is cleaned, placed in a plasma nitriding device, introduced with a mixed atmosphere of nitrogen and hydrogen in a ratio of 1:2, and heated to 500 °C for nitriding for 1.5 h, and then cooled to room temperature to obtain a three-dimensional porous high entropy alloy with a nitrided layer on the surface; S4. The three-dimensional porous high entropy alloy prepared in S3 is placed in a crucible with the aluminum alloy at the bottom and evacuated, heated to 400 ° C to preheat the three-dimensional porous high entropy alloy, and then heated to 720 ° C to melt the aluminum alloy and pressurize it with argon gas, and the temperature and pressure are maintained until the infiltration is completed and solidified to obtain an aluminum-based composite material; The aluminum alloy matrix comprises the following weight percentages: Zn: 5.55 wt%, Mg: 2.27 wt%, Cu: 1.43 wt%, Cr: 0.25 wt%, Fe: 0.15 wt%, Si: 0.05 wt%, and the balance is Al; The composition of the three-dimensional porous high entropy alloy is Ti 25 Mg 20 Fe 20 Cr 15 Ni 15 La5, and 1% Y2O3 was added.
[0037] Comparative Example 3: An aluminum-based composite material, consisting of 65% aluminum alloy matrix and 35% three-dimensional porous high-entropy alloy, wherein the three-dimensional porous high-entropy alloy is a three-dimensionally connected open-pore structure with a porosity of 65% and a 1-2 μm nitride layer on the surface; The preparation method of the aluminum-based composite material comprises the following steps: S1. The raw material powders required for high entropy alloy are prepared in proportion, and mechanical alloying ball milling is performed to mix them evenly. The ball milling speed is 320 r / min, and the ball milling time is 24 h. The pore-forming agent NaCl particles with a particle size of 200 ~ 300 μm and the binder anhydrous ethanol are added and ball milled again to mix them evenly and become a paste. The amount of pore-forming agent added is 125% of the volume of the metal powder, and the amount of binder added is 8% of the mass of the metal powder to obtain a uniform raw material; S2. The raw material prepared in S1 is placed in a mold, cold pressed and dried, and placed in a vacuum sintering furnace for pre-sintering at a temperature of 780 °C for 5 h. The pore-forming agent is removed in a water bath and dried. Then, a secondary sintering is performed by plasma discharge sintering at a temperature of 1250 °C for 4 h to obtain a three-dimensional porous high-entropy alloy. S3. The three-dimensional porous high entropy alloy prepared in S2 is cleaned, placed in a plasma nitriding device, introduced with a mixed atmosphere of nitrogen and hydrogen in a ratio of 1:2, and heated to 500 °C for nitriding for 1.5 h, and then cooled to room temperature to obtain a three-dimensional porous high entropy alloy with a nitrided layer on the surface; S4. The three-dimensional porous high entropy alloy prepared in S3 is placed in a crucible with the aluminum alloy at the bottom and evacuated, heated to 400 ° C to preheat the three-dimensional porous high entropy alloy, and then heated to 700 ° C to melt the aluminum alloy and pressurize it with argon gas, and the temperature and pressure are maintained until the infiltration is completed and solidified to obtain an aluminum-based composite material; The aluminum alloy matrix comprises the following weight percentages: Zn: 5.82 wt%, Mg: 2.37 wt%, Cu: 1.45 wt%, Cr: 0.19 wt%, Fe: 0.12 wt%, Si: 0.1 wt%, and the balance is Al; The composition of the three-dimensional porous high entropy alloy is Ti 25 Mg 20 Fe 20 Cr 15 Ni 15 La5, and 1% Y2O3 was added.
[0038] Comparative Example 4: An aluminum-based composite material, consisting of 65% aluminum alloy matrix and 35% three-dimensional porous high-entropy alloy, wherein the three-dimensional porous high-entropy alloy is a three-dimensionally connected open-pore structure with a porosity of 65% and a 1-2 μm nitride layer on the surface; The preparation method of the aluminum-based composite material comprises the following steps: S1. The raw material powders required for high entropy alloy are prepared in proportion, and mechanical alloying ball milling is performed to mix them evenly. The ball milling speed is 320 r / min, and the ball milling time is 24 h. The pore-forming agent NaCl particles with a particle size of 200 ~ 300 μm and the binder anhydrous ethanol are added and ball milled again to mix them evenly and become a paste. The amount of pore-forming agent added is 125% of the volume of the metal powder, and the amount of binder added is 8% of the mass of the metal powder to obtain a uniform raw material; S2. The raw material prepared in S1 is placed in a mold, cold pressed and dried, and placed in a vacuum sintering furnace for pre-sintering at a temperature of 780 °C for 5 h. The pore-forming agent is removed in a water bath and dried. Then, a secondary sintering is performed by plasma discharge sintering at a temperature of 1250 °C for 4 h to obtain a three-dimensional porous high-entropy alloy. S3. The three-dimensional porous high entropy alloy prepared in S2 is cleaned, placed in a plasma nitriding device, introduced with a mixed atmosphere of nitrogen and hydrogen in a ratio of 1:2, and heated to 500 °C for nitriding for 1.5 h, and then cooled to room temperature to obtain a three-dimensional porous high entropy alloy with a nitrided layer on the surface; S4. The three-dimensional porous high entropy alloy prepared in S3 is placed in a crucible with the aluminum alloy at the bottom and evacuated, heated to 400 ° C to preheat the three-dimensional porous high entropy alloy, and then heated to 800 ° C to melt the aluminum alloy and pressurize it with argon gas, and the temperature and pressure are maintained until the infiltration is completed and solidified to obtain an aluminum-based composite material; The aluminum alloy matrix comprises the following weight percentages: Zn: 5.67 wt%, Mg: 2.21 wt%, Cu: 1.47 wt%, Cr: 0.29 wt%, Fe: 0.13 wt%, Si: 0.05 wt%, and the balance is Al; The composition of the three-dimensional porous high entropy alloy is Ti 25 Mg 20 Fe 20 Cr 15 Ni 15 La5, and 1% Y2O3 was added.
[0039] Comparative Example 5: An aluminum-based composite material, consisting of 65% aluminum alloy matrix and 35% three-dimensional porous high-entropy alloy, wherein the three-dimensional porous high-entropy alloy is a three-dimensionally connected open-pore structure with a porosity of 65% and a 1-2 μm nitride layer on the surface; The preparation method of the aluminum-based composite material comprises the following steps: S1. The raw material powders required for high entropy alloy are prepared in proportion, and mechanical alloying ball milling is performed to mix them evenly. The ball milling speed is 320 r / min, and the ball milling time is 24 h. The pore-forming agent NaCl particles with a particle size of 200 ~ 300 μm and the binder anhydrous ethanol are added and ball milled again to mix them evenly and become a paste. The amount of pore-forming agent added is 125% of the volume of the metal powder, and the amount of binder added is 8% of the mass of the metal powder to obtain a uniform raw material; S2. The raw material prepared in S1 is placed in a mold, cold pressed and dried, and placed in a vacuum sintering furnace for pre-sintering at a temperature of 760 °C for 5 h. The pore-forming agent is removed in a water bath and dried. Then, a secondary sintering is performed by plasma discharge sintering at a temperature of 1250 °C for 4 h to obtain a three-dimensional porous high-entropy alloy. S3. The three-dimensional porous high entropy alloy prepared in S2 is cleaned, placed in a plasma nitriding device, introduced with a mixed atmosphere of nitrogen and hydrogen in a ratio of 1:2, and heated to 500 °C for nitriding for 1.5 h, and then cooled to room temperature to obtain a three-dimensional porous high entropy alloy with a nitrided layer on the surface; S4. The three-dimensional porous high entropy alloy prepared in S3 is placed in a crucible with the aluminum alloy at the bottom and evacuated, heated to 400 ° C to preheat the three-dimensional porous high entropy alloy, and then heated to 760 ° C to melt the aluminum alloy and pressurize it with argon gas, and the temperature and pressure are maintained until the infiltration is completed and solidified to obtain an aluminum-based composite material; The aluminum alloy matrix comprises the following components in weight percentage: Zn: 5.78 wt%, Mg: 2.47 wt%, Cu: 1.62 wt%, Cr: 0.21 wt%, Fe: 0.15 wt%, Si: 0.08 wt%, and the balance is Al; The composition of the three-dimensional porous high entropy alloy is Ti 25 Mg 20 Fe 20 Cr 15 Ni 15 La5, and 7% Y2O3 was added.
[0040] Comparative Example 6: An aluminum-based composite material, consisting of 65% aluminum alloy matrix and 35% three-dimensional porous high-entropy alloy, wherein the three-dimensional porous high-entropy alloy is a three-dimensionally connected open-pore structure with a porosity of 65% and a 1-2 μm nitride layer on the surface; The preparation method of the aluminum-based composite material comprises the following steps: S1. The raw material powders required for high entropy alloy are prepared in proportion, and mechanical alloying ball milling is performed to mix them evenly. The ball milling speed is 320 r / min, and the ball milling time is 24 h. The pore-forming agent NaCl particles with a particle size of 200 ~ 300 μm and the binder anhydrous ethanol are added and ball milled again to mix them evenly and become a paste. The amount of pore-forming agent added is 125% of the volume of the metal powder, and the amount of binder added is 8% of the mass of the metal powder to obtain a uniform raw material; S2. The raw material prepared in S1 is placed in a mold, cold pressed and dried, and placed in a vacuum sintering furnace for pre-sintering at a temperature of 760 °C for 5 h. The pore-forming agent is removed in a water bath and dried. Then, a secondary sintering is performed by plasma discharge sintering at a temperature of 1250 °C for 4 h to obtain a three-dimensional porous high-entropy alloy. S3. The three-dimensional porous high entropy alloy prepared in S2 is cleaned, placed in a plasma nitriding device, introduced with a mixed atmosphere of nitrogen and hydrogen in a ratio of 1:2, and heated to 500 °C for nitriding for 1.5 h, and then cooled to room temperature to obtain a three-dimensional porous high entropy alloy with a nitrided layer on the surface; S4. The three-dimensional porous high entropy alloy prepared in S3 is placed in a crucible with the aluminum alloy at the bottom and evacuated, heated to 400 ° C to preheat the three-dimensional porous high entropy alloy, and then heated to 760 ° C to melt the aluminum alloy and pressurize it with argon gas, and the temperature and pressure are maintained until the infiltration is completed and solidified to obtain an aluminum-based composite material; The aluminum alloy matrix comprises the following weight percentages: Zn: 5.79 wt%, Mg: 2.34 wt%, Cu: 1.55 wt%, Cr: 0.26 wt%, Fe: 0.07 wt%, and the balance is Al; The composition of the three-dimensional porous high entropy alloy is Ti 25 Mg 20 Fe 20 Cr 15 Ni 15 La5.
[0041] Comparative Example 7: An aluminum-based composite material, consisting of 65% aluminum alloy matrix and 35% three-dimensional porous high-entropy alloy, wherein the three-dimensional porous high-entropy alloy is a three-dimensionally connected open-pore structure with a porosity of 65%; The preparation method of the aluminum-based composite material comprises the following steps: S1. The raw material powders required for high entropy alloy are prepared in proportion, and mechanical alloying ball milling is performed to mix them evenly. The ball milling speed is 320 r / min, and the ball milling time is 24 h. The pore-forming agent NaCl particles with a particle size of 200 ~ 300 μm and the binder anhydrous ethanol are added and ball milled again to mix them evenly and become a paste. The amount of pore-forming agent added is 125% of the volume of the metal powder, and the amount of binder added is 8% of the mass of the metal powder to obtain a uniform raw material; S2. The raw material prepared in S1 is placed in a mold, cold pressed and dried, and placed in a vacuum sintering furnace for pre-sintering at a temperature of 760 °C for 5 h. The pore-forming agent is removed in a water bath and dried. Then, a secondary sintering is performed by plasma discharge sintering at a temperature of 1250 °C for 4 h to obtain a three-dimensional porous high-entropy alloy. S3. The three-dimensional porous high entropy alloy prepared in S2 is placed in a crucible with the aluminum alloy at the bottom and evacuated, heated to 400 ° C to preheat the three-dimensional porous high entropy alloy, and then heated to 760 ° C to melt the aluminum alloy and pressurize it with argon gas, and the temperature and pressure are maintained until the infiltration is completed and solidified to obtain an aluminum-based composite material; The aluminum alloy matrix comprises the following weight percentages: Zn: 5.94 wt%, Mg: 2.03 wt%, Cu: 1.35 wt%, Cr: 0.30 wt%, Fe: 0.06 wt%, Si: 0.05 wt%, and the balance is Al; The composition of the three-dimensional porous high entropy alloy is Ti 25 Mg 20 Fe 20 Cr 15 Ni 15 La5, and 3% Y2O3 was added.
[0042] Each embodiment and comparative example was prepared into a standard specimen with a circular cross section, and a universal testing machine was used for tensile testing. The tensile test method was carried out in accordance with GB / T 228.1-2021 standard, and the hardness was tested with a microhardness tester. The results are shown in Tables 1 to 5.
[0043] Table 1 Effects of different reinforcement phase volume fractions on the properties of aluminum matrix composites
[0044] Table 2 Effects of different porous high entropy alloy sintering temperatures on the properties of aluminum matrix composites
[0045] Table 3 Effects of different melting casting temperatures on the properties of aluminum matrix composites
[0046] Table 4 Effect of different Y2O3 addition amounts on the properties of aluminum-based composites
[0047] Table 5 Effect of nitriding layer on the properties of aluminum matrix composites
[0048] In summary, all embodiments of the present invention have high strength and hardness, excellent comprehensive mechanical properties, and broad application prospects.
Claims
1. A three-dimensional porous high entropy alloy reinforced aluminum-based composite material, characterized in that: The aluminum-based composite material consists of 60-70% aluminum alloy matrix and 30-40% three-dimensional porous high-entropy alloy, wherein the three-dimensional porous high-entropy alloy is a three-dimensionally connected open-pore structure with a porosity of 60-70% and a 1-2 μm nitride layer on the surface.
2. The method for preparing the three-dimensional porous high entropy alloy reinforced aluminum-based composite material according to claim 1, characterized in that: The following steps are involved: S1. The raw material powders required for the high entropy alloy are prepared in proportion, and are evenly mixed by mechanical alloying and ball milling. The pore former and the binder are evenly mixed by ball milling again and become a paste to obtain a uniform raw material; S2. The raw material prepared in S1 is placed in a mold, cold pressed and dried, placed in a vacuum sintering furnace for pre-sintering, the pore-forming agent is removed in a water bath and dried, and then secondary sintered by plasma discharge sintering to obtain a three-dimensional porous high entropy alloy; S3. The three-dimensional porous high entropy alloy prepared in S2 is cleaned, placed in a plasma nitriding device, introduced into a mixed atmosphere of hydrogen and nitrogen and heated for nitridation, and then cooled to room temperature to obtain a three-dimensional porous high entropy alloy having a nitrided layer on the surface; S4. Place the three-dimensional porous high entropy alloy prepared in S3 at the bottom and the aluminum alloy at the top in a crucible and evacuate the crucible, preheat the three-dimensional porous high entropy alloy, then heat to melt the aluminum alloy and fill it with argon to pressurize it, maintain the temperature and pressure until the infiltration is completed and then solidify to obtain a three-dimensional porous high entropy alloy reinforced aluminum-based composite material.
3. The method for preparing the three-dimensional porous high entropy alloy reinforced aluminum-based composite material according to claim 2, characterized in that: The mechanical alloying ball milling speed in step S1 is 300 to 350 r / min, and the ball milling time is 20 to 24 h.
4. The method for preparing the three-dimensional porous high entropy alloy reinforced aluminum-based composite material according to claim 2, characterized in that: In step S1, the pore-forming agent is NaCl, the particle size is 200-300 μm, and the amount of NaCl added is 100-150% of the volume of the metal powder; the binder is anhydrous ethanol, and the amount of anhydrous ethanol added is 7-10% of the mass of the metal powder.
5. The method for preparing the three-dimensional porous high entropy alloy reinforced aluminum-based composite material according to claim 2, characterized in that: In step S2, the pre-sintering temperature is 750-800 °C, and the holding time is 4-6 h; the secondary sintering temperature is 1100-1300 °C, and the holding time is 3-5 h.
6. The method for preparing the three-dimensional porous high entropy alloy reinforced aluminum-based composite material according to claim 2, characterized in that: The heating temperature in step S3 is 480-520° C., the nitriding time is 1-2 h, and the ratio of nitrogen to hydrogen in the mixed atmosphere is 1:1-2.
7. The method for preparing the three-dimensional porous high entropy alloy reinforced aluminum-based composite material according to claim 2, characterized in that: In step S4, the preheating temperature of the three-dimensional porous high entropy alloy is 400-420°C, and the heating temperature of the molten aluminum alloy is 720-780°C.
8. The three-dimensional porous high entropy alloy reinforced aluminum-based composite material according to claim 1, characterized in that: The components of the aluminum alloy matrix are composed of the following weight percentages: Zn: 5.5 ~ 6.0 wt%, Mg: 2.0 ~ 2.5 wt%, Cu: 1.3 ~1.7 wt%, Cr: 0.15 ~ 0.33 wt%, Fe: ≤0.15 wt%, Si: ≤0.1 wt%, and the balance is Al.
9. The three-dimensional porous high entropy alloy reinforced aluminum-based composite material according to claim 1, characterized in that: The composition of the three-dimensional porous high entropy alloy is Ti 20-25 Mg 20-25 Fe 15-20 Cr 15-20 Ni 10-15 La 5-10 , and 1 ~ 5% Y2O3 was added.
Citation Information
Patent Citations
Ceramic particle reinforced aluminum base composite material with medium and low volume fractions and preparation method of composite material
CN104232973A
Porous high-entropy alloy and preparation method thereof
CN105624455A
Oxide dispersion strengthened (ODS) high-entropy alloy and preparation method thereof
CN106435323A
Mg-based high-entropy reversible hydrogen storage alloy and preparation method thereof
CN107739936A
Nano / submicron double-scale oxide reinforced refractory high-entropy alloy composite material and preparation method thereof
CN115679177A